ORAL TEST: A POWERFUL TOOL FOR ASSESSING STUDENTS' ACTUAL ACHIEVEMENT IN LANGUAGE LEARNING - Muhamad Ahsanu (Soegijapranata Catholic University, 2013)
Teaching and testing are inseparable elements in pedagogical world irrespective of the course a teacher teaches. Phrased differently, there is no teaching without testing and vice versa. The results of testing should ideally motivate students in learning and give better perspectives to teachers on _how to devise a better teaching-learning. Accordingly, a teacher needs a sort of test that can sufficiently assess students' actual achievement in learning, in their given courses. One of which is so-called